The effect of the glass planes on thermal comfort in office buildings: a case study - Muhammad Syarif Hidayat; Sri Mulyani (International Journal of Built Environment and Scientific Research, 2023)
One of the most important aspect in architecture is the selection of exterior material. This materialsurface faces directly with building’s surrounding climate and environment, transferring the heat through its wall and roof significantly so it requires more consideration from the planners. Widely use of glasses as building’s exterior impacts its heat absorbing thereby it needs more power for air conditioning in order to keep the interior temperature productively workable. The objective of this research is to observe the impact between glass partition and interior thermal condition, how the habitants react, and also the ideal temperature for both users and building’s OTTV. Correlational research combines results from thermal observation and user’s perceptionin order to get its convenience thermal condition and to know its OTTV so we can issue the standard